Differential Impact of Customer Equity Drivers on Satisfaction: The Case of China’s Telecommunications Industry - Seo, HaeJin; Fu, Linlin; Song, Tae Ho (Asia Marketing Journal (Online), 2023)
As the necessity of customer relationship management (CRM) increases, measuring the performance of CRM have been actively discussed. Customer equity (CE) is regarded as an appropriate indicator for evaluating the outcomes of marketing activities. There are three drivers of CE: brand, value, and relationship equity. This study aims to investigate the impact of three drivers on customer satisfaction. Market competition is an environmental factor that affects the effectiveness of CRM. This study divides target firms into leaders and followers. This study found that the differential impact of CE drivers on customer satisfaction depends on the firm’s status (leader or follower). Specifically, the brand equity driver significantly impacts the leader firm. However, the impacts of value and relationship equity drivers are bigger for follower firms. The above results suggest that firms need to build CRM strategies that consider the competitive situation of the market and their position.